A Proposal to Evaluate Training Material of Indonesia mengajar Program; Case Study: Training for Pengajar Muda Batch Fourth - Yuliana, Indah; Gustomo, Aurik (Journal of Business and Management, 2014)
Abstract-PMâ€™s workplace condition is very dynamic so IM need to evaluate the intensive training implementation periodically in order to the trained material to PM appropriate with the needs. This research aim to evaluate intensive training implementation which was gave to PM batch fourth. This research focus on evaluation of training PM batch fourth. Result from the research will be recommend to IM to be a consideration for the next training design. This research use qualitative method which use primary and secondary data. The primary data was gathered by interview and the secondary data was gathered from journal published, internet and data from IM which related with the research. Based on the data analysis, the results showed that there is a gap between the materials needed with the material that has been given at the intensive training. There are several competencies need more training, those are pedagogical understanding, knowledge about condition of the placement, survival skills, and leadership skills. To cover this gap, IM need to add the necessary materials and remove the less important training material.Â Keywords: education, training, competency, evaluation, IM, PM